Characterization of 0.93Pb(Zn1/3Nb2/3)O 3-0.07BaTiO3 ceramics derived from a novel Zn 3Nb2O8 B-site precursor - Pakawanit P. (2014)
In this work, perovskite relaxor ferroelectric lead zinc niobate-barium titanate (0.93PZN-0.07BT) ceramics were fabricated by using a combination of Zn3Nb2O8 B-site precursor and reactive sintering process. The effects of sintering condition on phase formation, densification, microstructure and dielectric properties of the final products have been investigated using a combination of X-ray diffraction, Archimedes density measurement, scanning electron microscopy and dielectric measurement techniques. It is seen that pure perovskite phase of PZN-BT solid solutions can be achieved in all samples. Density and average grain size values of sintered samples increased with sintering temperatures and dwell time. With appropriate sintering at 1150 °C for 5 h, 0.93PZN-0.07BT ceramics exhibited a peak dielectric constant of 11,497 and dielectric loss of 0.05 at the Curie temperature of 99 °C measured at 1 kHz. © 2012 Elsevier Ltd and Techna Group S.r.l.